Progressive Legal Analysis of The Copyright Infringement Case of Agnes Monica Versus Ari Bias - Utama, Mohammad Wira (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
The introduction above shows that this study has the aim of comprehensively analyzing from a progressive legal perspective in the case of copyright infringement of Ari Bias Versus Agnez Mo. This research is a qualitative study with a descriptive approach, namely an approach that has special characteristics, namely using descriptive sentences in explaining one by one the main topics used in this study. The data used in this study are secondary data that researchers obtained from various credible sources such as books, scientific articles, credible websites, and various other sources commonly used in research. The data were analyzed by stages of data collection, data selection, data reduction, and drawing conclusions. The conclusion in this article show